Managing fodder and forage genetic resources - International Livestock Research Institute (International Livestock Research Institute, 2008)
This Other contains two films about the ILRI gene Bank in Ethiopia, each 10 minutes in length. The first one, 'Conserving Fodder and Forage Crops' is about saving forage crops for livestock and their keepers. The second film 'Using Fodder and Forage Crops' presents a colorful film - from germplasm to feed - putting ILRI's gene bank to work.